Phytochemical Screening by FTIR Spectroscopic Analysis and Antibacterial Activity of Sesbania grandiflora - Ndahawali, Suryaningsih; Andayani, Sri; Hardoko, Hardoko (The Journal of Experimental Life Science, 2019)
Sesbania grandiflora is a medicinal plant that has been used by many Indonesian people. They have the ability as antibacterial because they contain bioactive compounds that inhibit bacterial growth. Sesbania grandiflora also contains other active compounds such as tannins, saponins, steroids, flavonoids, and terpenoids. This study aims to determine the antibacterial activity of extracts, n-hexane fraction, ethyl acetate fraction and water fraction of Sesbania grandiflora against Edwardsiella tarda using the well diffusion method in different concentration (75 ppm, 150 ppm dan 225 ppm), and knowing the active compounds of FTIR absorption bands. MIC (minimum inhibitory concentration) value of extract, n-hexane, ethyl acetate, and water fractions respectively was 0.51 %, 1.11 %, 0.97 %, dan 0.79 %. InIibitory zone diameter of the n-hexane fraction is most active against Edwardsiella tarda bacteria. The results of FTIR identification showed that n-hexane fraction contained flavonoids and terpenoids, as seen from absorption bands that function as antibacterial compounds.Keywords: antibacterial, Edwardsiella tarda, FTIR, Phytochemical Sesbania grandiflora.